Segmented copolymer well wall reinforcer rich in positive charge anchor points as well as preparation method and application of segmented copolymer well wall reinforcer
By preparing a block copolymer wellbore reinforcing agent rich in positively charged anchor points, the problem of poor sealing performance of existing wellbore reinforcing agents under high temperature and high pressure conditions was solved, achieving efficient plugging and wellbore protection in shale formations, and improving drilling safety and efficiency.
Patent Information
- Application Number
- CN202511691321.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-01-02
AI Technical Summary
Existing wellbore strengthening agents are difficult to form a continuous and dense protective layer in shale formations under high temperature and high pressure conditions. They have poor sealing performance, insufficient durability, and cannot effectively solve the problem of well leakage. Furthermore, they have a narrow range of applications and cannot be widely used in complex formations.
A block copolymer wellbore reinforcing agent with positively charged anchor points is used. It generates a silicon-oxygen bond polymer through an acid-catalyzed hydrolysis polymerization reaction, and grafts hydrophilic groups and quaternary ammonium salt groups to form a block copolymer, which enhances the wellbore's adsorption and chemical stability.
It maintains high-efficiency plugging performance under high temperature and high pressure environments, significantly improves the safety and efficiency of drilling operations, prevents wellbore collapse and secondary leakage, and is suitable for low-permeability fractured reservoirs, porous and fractured leakage formations.
Smart Images

Figure BDA0005692784290000031 
Figure BDA0005692784290000032 
Figure BDA0005692784290000041
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a copolymer well wall reinforcing agent, in particular to a block copolymer well wall reinforcing agent rich in positive charge anchor points, and also relates to a preparation method of the block copolymer well wall reinforcing agent rich in positive charge anchor points, and also relates to the application of the block copolymer well wall reinforcing agent rich in positive charge anchor points, and belongs to the technical field of new materials for drilling engineering. BACKGROUND
[0002] With the vigorous promotion of shale gas and shale oil exploration and development by the country, the complexity of shale formation structure brings serious challenges to oil drilling engineering. Among them, the problem of lost circulation is particularly prominent, which has become a major challenge for engineering and technical personnel. Lost circulation not only leads to a large loss of drilling fluid and increases drilling costs, but also can cause serious safety problems and operation delays.
[0003] Lost circulation is usually manifested as the loss of drilling fluid through the cracks or pores of the well wall into the formation during drilling. This can cause the well wall to collapse, causing the drilling equipment to be stuck (stuck pipe), and even causing extreme accidents such as blowout, posing a serious threat to personnel safety and equipment integrity. The complexity of the problem of lost circulation lies in its multi-factor coupling. As the drilling depth increases, the temperature and pressure of the downhole environment rise sharply, and lost circulation can be caused by natural fractures, porosity loss or human operation of the formation. Therefore, the development of efficient well wall reinforcing materials has become a core task to solve the above problems.
[0004] The current mainstream well wall reinforcing system - silicate-based slurry, calcium carbonate-polyurethane core-shell microspheres, deep well broken formation repair agent and zwitterionic polymer / polyol composite formula - has its own advantages in terms of temperature resistance, plugging strength or interfacial adhesion, but they all have the common defect of insufficient function-environment adaptability: silicate-based materials have good high-temperature stability, but the cured film is brittle and has low interfacial peeling energy; calcium carbonate-polyurethane microspheres have thermal deformation ability, but they are prone to selective plugging in heterogeneous pore throats and fail; deep well repair agents rely on high crosslinking density to obtain high adhesion strength, but the toughness of the cured material drops sharply, and microcrack propagation easily induces secondary loss; zwitterionic polymers rely on electrostatic / hydrogen bond cooperative adsorption, and under high temperature and high pressure conditions, charge shielding and chain segment relaxation coexist, leading to rapid desorption of the adsorption layer. In view of the inherent characteristics of low negative surface charge density and lack of hydrophilic groups of shale, it is difficult for the above-mentioned materials to form a continuous and dense protective layer, and the durability of well wall reinforcement is limited.
[0005] The Chinese invention patent with publication number CN 118652671B discloses a "well wall strengthening agent composition and water-based drilling fluid and its preparation method", the well wall strengthening agent composition is composed of the following components by weight: cationic modified nano plugging agent 1-3 parts, nano emulsion 1-3 parts, ceramic powder 2-6 parts, and short-cut fiber 1-3 parts. The cationic modified nano plugging agent is composed of the following components by weight: nano silicon dioxide 20-30 parts, silane coupling agent 20-30 parts, substitution agent 8-12 parts, catalyst A 10-15 parts, initiator 5-10 parts, ionic liquid 30-40 parts, catalyst B 1-3 parts, and non-ionic monomer 15-20 parts. The defects of the patent are as follows: 1. The function-environment adaptability is not good, and the shale formation characteristics are not specially designed, it is difficult to form a continuous and dense protective layer in the shale formation, and the well wall strengthening durability is limited. 2. The plugging performance is not comprehensive, the plugging effect on complex cracks and pore structure in shale formation is not good; the durability is poor, the stability of the plugging layer is insufficient under high temperature and high pressure conditions; the adaptability and universality are narrow, mainly suitable for coalbed methane drilling, and the adaptability to complex formation conditions in shale gas and shale oil exploration and development is not wide enough. 3. The comprehensive performance is not superior, it cannot better solve the problems of well leakage and well wall strengthening in shale gas and shale oil exploration and development; the economic efficiency is not obvious, the cost performance may be low, it cannot effectively improve the drilling efficiency and safety, and reduce the drilling cost; the safety is low, it cannot effectively prevent well wall collapse and secondary loss, and reduce the probability of extreme accidents such as blowout.
[0006] The Chinese invention patent with publication number CN 120647863A discloses a "film-forming strengthening agent for water-based drilling fluid, its preparation method and slim hole reservoir protection drilling fluid", including the following steps: A) mixing phenolic compounds, water and inorganic base, adjusting pH value, adding silicon reagent, and reacting to obtain a first reaction liquid; B) mixing phenol, formaldehyde, sulfonated reagent and the first reaction liquid, and reacting to obtain a second reaction liquid; C) mixing the second reaction liquid and water to obtain a dilution liquid, and reacting to obtain a third reaction liquid; cooling and drying the third reaction liquid to obtain the film-forming strengthening agent. The film-forming strengthening agent is a silicon-modified sulfonated phenolic aldehyde resin, which is prepared by reacting water-soluble silicate, phenolic compounds, formaldehyde, sulfonic acid reagent and inorganic base under high temperature and high pressure. The defects of the patent are as follows: although it can improve the mud cake quality and control the high temperature and high pressure filtration loss, it does not specifically design for the characteristics of the low negative surface charge density and lack of hydrophilic groups of shale formation, it is difficult to form a continuous and dense protective layer in the shale formation, and the well wall strengthening durability is limited. In shale formation, it may not be able to achieve precise plugging for complex cracks and pore structure, especially heterogeneous pore throat. SUMMARY
[0007] This section is intended to summarize some aspects of the embodiments of the present application and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the summary of the description and the title of the application, and such simplifications or omissions cannot be used to limit the scope of the present application.
[0008] In view of the above and / or the problems existing in the prior art that water-based drilling fluid often encounters shale instability accidents, the present application is proposed.
[0009] The primary purpose of the present application is to overcome the problems existing in the prior art, provide a block copolymer well wall strengthening agent with rich positive charge anchor points, which has excellent well wall adsorption and chemical stability, can maintain high efficiency in high temperature and high pressure environment, effectively reduces the erosion of drilling fluid to the well wall, and performs well in low permeability fracture reservoir, pore type and fractured leakage formation and other complex formations, significantly improves the safety and efficiency of drilling operation.
[0010] To solve the above technical problems, the block copolymer well wall strengthening agent with rich positive charge anchor points of the present application is a block copolymer formed by generating a siloxane bond polymer through acid catalytic hydrolysis polymerization reaction, and then grafting hydrophilic groups and introducing quaternary ammonium salt groups in sequence.
[0011] Further, the siloxane bond polymer is prepared by hydrolysis condensation reaction of silane monomers including dimethyldichlorosilane, dimethyldimethoxysilane or dimethyldiethoxysilane.
[0012] Further, the molecular formula of dimethyldichlorosilane, dimethyldimethoxysilane and dimethyldiethoxysilane is respectively:
[0013]
[0014] The molecular formula of the siloxane bond polymer is:
[0015]
[0016] Further, the hydrophilic group is polyethylene glycol or polypropylene glycol, and the molecular formula is respectively:
[0017]
[0018] Further, the quaternary ammonium salt group is dimethyldiallylammonium chloride, hydroxyethyltrimethylammonium chloride or hydroxyethyltriethylammonium chloride, and the molecular formula is respectively:
[0019]
[0020] Another object of the present application is to overcome the problems in the prior art and provide a preparation method of a block copolymer well wall strengthener with positive charge anchor points, which has excellent well wall adsorption and chemical stability, can maintain high efficiency in plugging performance under high temperature and high pressure environment, effectively reduces the erosion of drilling fluid to the well wall, and performs well in low permeability fractured reservoir, pore type and fractured leakage formation and other complex formations, significantly improving the safety and efficiency of drilling operation.
[0021] To solve the above technical problems, the preparation method of the block copolymer well wall strengthener with positive charge anchor points comprises the following steps in sequence:
[0022] S1, preparing a siloxane polymer;
[0023] S2, preparing a quaternary ammonium siloxane polymer;
[0024] S3, grafting a hydrophilic group;
[0025] S4, further introducing a quaternary ammonium salt group to synthesize the block copolymer with positive charge anchor points.
[0026] Further, the specific preparation process of the siloxane polymer in step S1 is as follows: dimethyldichlorosilane or dimethyldimethoxysilane or dimethyldiethoxysilane is subjected to acid catalytic reaction with dimethylhydridochlorosilane or dimethylhydridomethoxysilane or dimethylhydridodiethoxysilane in a solvent, the solvent is dichloromethane or toluene, and after the acid catalytic reaction, the acid water layer is separated by standing; then the oil layer is repeatedly washed with distilled water until the pH value of the washed water is 7; finally, the oil layer is dried under vacuum to remove the contained water, and the siloxane polymer is obtained.
[0027] Further, in step S1, the molar ratio of silane monomer to hydrogen-containing silane is (5-20):2; the acid catalyst is hydrochloric acid or sulfuric acid, and the amount of the acid catalyst is 10%-20% of the mass of the reaction system, and the reaction time is 5-8 hours.
[0028] Further, the reaction process of generating the siloxane polymer is as follows:
[0029]
[0030] Further, in step S2, dichloromethane or toluene is used as the solvent, and the siloxane polymer obtained in step S1 is subjected to a silicon-hydrogen bond double bond addition reaction under the catalysis of chloroplatinic acid to obtain a quaternary ammonium siloxane polymer.
[0031] Further, in step S2, the molar ratio of the siloxane polymer to the quaternary ammonium salt group is (2-6):1, the amount of the chloroplatinic acid catalyst is 3ppm-6ppm, and the reaction time is 4-6 hours.
[0032] Further, the reaction process for generating the quaternary ammonium siloxane polymer is as follows:
[0033]
[0034] Further, in step S3, the quaternary ammonium siloxane polymer obtained in step S2 is reacted with the hydrophilic group polyethylene glycol or polypropylene glycol in dichloromethane or toluene as a solvent under the catalysis of sodium ethoxide or sodium methoxide to obtain the quaternary ammonium siloxane polymer grafted with the hydrophilic group.
[0035] Further, in step S3, the molar ratio of the quaternary ammonium siloxane polymer to the hydrophilic group is 1:2, and the catalytic reaction is carried out under the catalysis of sodium methoxide or sodium ethoxide at 80-100℃ for 5-8 hours, and the catalyst is used in an amount of 5%-15% of the mass of the reaction system.
[0036] Further, the reaction process for grafting the hydrophilic group is as follows:
[0037]
[0038] Further, in step S4, the quaternary ammonium siloxane polymer grafted with the hydrophilic group is reacted with the quaternary ammonium salt group hydroxyethyl trimethyl ammonium chloride or hydroxyethyl triethyl ammonium chloride in dichloromethane or toluene as a solvent under the catalysis of sodium hydroxide to obtain the block copolymer with the rich positive charge anchor point.
[0039] Further, in step S4, the molecular formulae of hydroxyethyl trimethyl ammonium chloride and hydroxyethyl triethyl ammonium chloride are as follows:
[0040]
[0041] The molar ratio of the quaternary ammonium siloxane polymer grafted with the hydrophilic group to the quaternary ammonium salt group is 1:2, the catalyst used is 5-10% of sodium hydroxide, and the reaction is carried out at 80-100℃ and under a pressure of 5MPa for 5-8 hours.
[0042] Further, the synthesis process for further introducing the quaternary ammonium salt group in step S4 is as follows:
[0043]
[0044] Another object of the present application is to overcome the problems in the prior art and provide an application of the block copolymer with the rich positive charge anchor point as a well wall strengthening agent. The well wall strengthening agent has excellent well wall adsorption and chemical stability, can maintain high efficiency in plugging performance under high temperature and high pressure environment, effectively reduces the erosion of drilling fluid to the well wall, and performs well in complex strata such as low-permeability fractured reservoirs, pore-type and fractured leakage strata, and significantly improves the safety and efficiency of drilling operations.
[0045] To solve the above technical problems, the application of the block copolymer well wall strengthener with positive charge anchors, which is added to the water-based drilling fluid in an amount of 3% to 6% of the total mass of the water-based drilling fluid, is used for well wall strengthening and plugging in shale formations.
[0046] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application at least include:
[0047] 1. In the water-based drilling fluid used for shale wells, there are multiple cations. These cations can interact with the multi-layer structure of clay and shale. Shale itself has a complex multi-layer structure with a negative charge on its surface. The positive charge anchors can be attracted by these negative charges and thus adsorbed on the shale layer. With the adsorption of multiple positive charge anchors, they form a uniform coating on the surface of the shale layer. This uniform coating acts like a protective film, which can protect the shale to some extent, preventing adverse effects from external factors, and providing a good foundation for subsequent drilling processes.
[0048] 2. The hydrophobic chain segments in the drilling fluid, such as siloxane segments, play an important role. These hydrophobic chain segments can prevent the shale from absorbing too much water. When the drilling fluid comes into contact with the shale, the hydrophobic chain segments will use their hydrophobicity to prevent water from penetrating too much into the interior of the shale. At the same time, multiple positive charge anchors are tightly bound to the shale through electrostatic attraction. This electrostatic attraction allows the hydrophobic chain segments to adhere more stably to the surface of the shale, further enhancing the protection of the shale. In this way, it can effectively prevent the shale from reducing its strength due to excessive water absorption, thereby ensuring the smooth progress of the drilling process and avoiding problems such as well wall collapse caused by insufficient shale strength.
[0049] 3. The hydrophilic group macromolecular alcohol plays a key role in the water-based drilling fluid. It can effectively dissolve the entire drilling fluid system in a water-based environment. The hydrophilic group of the macromolecular alcohol can form good interaction with water molecules, thereby uniformly dispersing the components of the drilling fluid in water. In addition, the macromolecular alcohol itself can also act as an adsorption site and be adsorbed on the shale layer. Its interaction with the shale surface further enhances the binding ability of the drilling fluid to the shale. This combination not only helps to stabilize the shale layer, but also allows the drilling fluid to better perform its functions in the drilling process, such as lubrication and carrying of cuttings, thereby improving drilling efficiency and safety.
[0050] 4、The well wall strengthening agent prepared by the method has stable performance in high temperature downhole environment, can maintain good performance under high temperature and high pressure conditions, and provides a hydrophobic film to prevent shale from absorbing water and swelling and collapsing; the introduction of the hydrophilic group significantly improves the solubility and dispersibility of the well wall strengthening agent in the water-based drilling fluid; the quaternary ammonium salt group has a positive charge, can form electrostatic adsorption with negative charge sites on the well wall surface (such as the surface of clay minerals), and thus significantly enhances the binding force between the well wall strengthening agent and the well wall. The integration of the three functions of "high temperature stability-interfacial wetting-charge compensation" is achieved. DETAILED DESCRIPTION
[0051] The application will be further described in conjunction with the following examples, but the examples are not a limitation on the technical solutions of the application. Any person skilled in the art can use the content of the application as a reference to appropriately change raw materials, process conditions and other aspects to achieve corresponding other purposes within the technical range disclosed by the application, and all changes do not deviate from the content of the application, all similar replacements and changes are considered to be within the scope of the application.
[0052] In order to better explain the application, the main content of the application will be further illustrated in conjunction with specific laboratory examples, but the content of the application is not limited to the following examples.
[0053] Secondly, the "one embodiment" or "embodiment" referred to herein means that a specific feature, structure or characteristic can be included in at least one implementation of the application. "In one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an independent or alternative embodiment that excludes other embodiments.
[0054] Example 1
[0055] S1, preparing a siloxane polymer;
[0056] After 5 hours of reaction of 5 mol of dimethyl dichlorosilane and 2 mol of dimethyl hydrogen chlorosilane in 2 L of dichloromethane as a solvent under the catalysis of 10% hydrochloric acid, the acid water layer is separated and removed, and an oil layer coated siloxane polymer solution is obtained; then the oil layer is repeatedly washed with distilled water until the pH value of the washed water is 7; finally, the oil layer is dried under vacuum to remove the contained water, and a siloxane polymer powder is obtained.
[0057] S2, preparing a quaternary ammonium siloxane polymer;
[0058] The quaternary ammonium siloxane polymer obtained above was reacted with the hydrophilic group polyethylene glycol in 1 L of dichloromethane as a solvent, and the molar ratio of the quaternary ammonium siloxane polymer to the hydrophilic group was 1:2. Sodium methoxide was used as a catalyst, the amount of the catalyst was 5% of the mass of the reaction system, and the catalytic reaction was carried out at 80°C for 5 hours to obtain the quaternary ammonium siloxane polymer grafted with the hydrophilic group.
[0059] S3, grafting a hydrophilic group;
[0060] The quaternary ammonium siloxane polymer obtained above was reacted with the hydrophilic group polyethylene glycol in 1 L of dichloromethane as a solvent, and the molar ratio of the quaternary ammonium siloxane polymer to the hydrophilic group was 1:2. Sodium methoxide was used as a catalyst, the amount of the catalyst was 5% of the mass of the reaction system, and the catalytic reaction was carried out at 80°C for 5 hours to obtain the quaternary ammonium siloxane polymer grafted with the hydrophilic group.
[0061] S4, further introducing a quaternary ammonium salt group to synthesize the block copolymer with the positively charged anchor point;
[0062] The quaternary ammonium siloxane polymer grafted with the hydrophilic group was catalytically reacted with the quaternary ammonium salt group, hydroxyethyl trimethyl ammonium chloride, in 1 L of dichloromethane as a solvent, and the molar ratio of the quaternary ammonium siloxane polymer grafted with the hydrophilic group to the quaternary ammonium salt group was 1:2. Sodium hydroxide was used as a catalyst, and the catalytic reaction was carried out at 80°C and 5 MPa for 5 hours to obtain the final product, i.e., the block copolymer with the positively charged anchor point.
[0063] Example Two
[0064] S1, preparing a siloxane polymer;
[0065] After 10 mol of dimethyl dimethoxysilane and 2 mol of dimethyl hydrodimethoxysilane were catalytically reacted in 3 L of toluene as a solvent and 15% of sulfuric acid for 6 hours, the acid water layer was separated and removed, and a siloxane polymer solution coated with an oil layer was obtained. Then, the oil layer was repeatedly washed with distilled water until the pH value of the washed water was 7. Finally, the oil layer was dried under vacuum to remove the contained water, and a siloxane polymer powder was obtained.
[0066] S2, preparing a quaternary ammonium siloxane polymer;
[0067] The quaternary ammonium siloxane polymer obtained above was reacted with the hydrophilic group polyethylene glycol in 1 L of dichloromethane as a solvent, and the molar ratio of the quaternary ammonium siloxane polymer to the hydrophilic group was 1:2. Sodium methoxide was used as a catalyst, the amount of the catalyst was 5% of the mass of the reaction system, and the catalytic reaction was carried out at 80°C for 5 hours to obtain the quaternary ammonium siloxane polymer grafted with the hydrophilic group.
[0068] S3, grafting a hydrophilic group;
[0069] The quaternary ammonium siloxane polymer obtained above is reacted with hydrophilic group polyethylene glycol in 3L dichloromethane solvent, the molar ratio of quaternary ammonium siloxane polymer to hydrophilic group is 1:2, sodium methoxide is used as catalyst, the amount of catalyst is 15% of the mass of the reaction system, and the catalytic reaction is carried out for 8 hours to obtain the quaternary ammonium siloxane polymer grafted with hydrophilic groups.
[0070] S4, further introducing quaternary ammonium salt groups to synthesize the block copolymer with positively charged anchor points;
[0071] The quaternary ammonium siloxane polymer grafted with hydrophilic groups is catalytically reacted with quaternary ammonium salt group hydroxyethyl triethyl ammonium chloride in 2L toluene solvent, the molar ratio of quaternary ammonium siloxane polymer grafted with hydrophilic groups to quaternary ammonium salt group is 1:2, the catalyst used is 7% sodium hydroxide, and the reaction is carried out at 90°C and 5MPa for 6 hours to obtain the final product, i.e. the block copolymer with positively charged anchor points.
[0072] Example Three
[0073] S1, preparing a siloxane polymer;
[0074] After 20 mol of dimethyldiethoxysilane is catalytically reacted with 2 mol of dimethylhydroethoxysilane in 5L dichloromethane as solvent and 20% hydrochloric acid for 8 hours, the acid water layer is separated and removed, and a siloxane polymer solution coated with an oil layer is obtained; then the oil layer is repeatedly washed with distilled water until the pH value of the washed water is 7; finally, the oil layer is dried under vacuum to remove the contained water, and a siloxane polymer powder is obtained.
[0075] S2, preparing a quaternary ammonium siloxane polymer;
[0076] The 6 mol of siloxane polymer obtained above is subjected to a silicon-hydrogen bond double bond addition reaction in 3L dichloromethane as solvent and 6 ppm chloroplatinic acid as catalyst, and the reaction is carried out for 6 hours to obtain a quaternary ammonium siloxane polymer.
[0077] S3, grafting a hydrophilic group;
[0078] The quaternary ammonium siloxane polymer obtained above is reacted with hydrophilic group polyethylene glycol in 3L dichloromethane solvent, the molar ratio of quaternary ammonium siloxane polymer to hydrophilic group is 1:2, sodium methoxide is used as catalyst, the amount of catalyst is 15% of the mass of the reaction system, and the catalytic reaction is carried out for 8 hours to obtain the quaternary ammonium siloxane polymer grafted with hydrophilic groups.
[0079] S4, further introducing quaternary ammonium salt groups to synthesize the block copolymer with positively charged anchor points;
[0080] The quaternary ammonium siloxane polymer grafted with hydrophilic groups and the quaternary ammonium salt group hydroxyethyl trimethyl ammonium chloride are catalytically reacted in 3L dichloromethane solvent, the molar ratio of the quaternary ammonium siloxane polymer grafted with hydrophilic groups and the quaternary ammonium salt group is 1:2, the catalyst used is 10% sodium hydroxide and the reaction is carried out at 100°C, 5MPa for 8 hours to obtain the final product, i.e. the positively charged anchor block copolymer.
[0081] Comparative Example One
[0082] Water-based drilling fluid: 5% bentonite + 1% lignosulfonate SPNH, 5‰ sulfomethyl phenolic resin type I SMP-1, 3‰ polyacrylic acid methyl, 2‰ polyanionic cellulose PAC, and about 1 / 10,000 caustic soda is added to adjust the pH value to 9.
[0083] Example Four
[0084] The well wall strengthening agent obtained in Example One is added to the water-based drilling fluid of Comparative Example One, and the amount of the well wall strengthening agent added is 6% of the total mass of the water-based drilling fluid, which is used for well wall strengthening and plugging in shale formations.
[0085] Example Five
[0086] The well wall strengthening agent obtained in Example Two is added to the water-based drilling fluid of Comparative Example One, and the amount of the well wall strengthening agent added is 4% of the total mass of the water-based drilling fluid, which is used for well wall strengthening and plugging in shale formations.
[0087] Example Six
[0088] The well wall strengthening agent obtained in Example Three is added to the water-based drilling fluid of Comparative Example One, and the amount of the well wall strengthening agent added is 3% of the total mass of the water-based drilling fluid, which is used for well wall strengthening and plugging in shale formations.
[0089] The performance of the product of the present application is verified as follows:
[0090] I. Viscosity Test
[0091] The viscosity of the drilling fluid under a certain shear rate is measured by a rotary viscometer. According to the standard test of Chapter 6 of GB / T16783.1-2014 "Petroleum and Natural Gas Industry Drilling Fluids Field Testing Part 1: Water-based Drilling Fluids", the viscosities before and after aging at 180°C for 10h are tested respectively. The viscosity performance evaluation test results of the block copolymer well wall strengthening agent with positively charged anchors provided in the examples of the present application are shown in Table 1:
[0092] Table 1
[0093]
[0094] Viscosity is an important parameter for measuring internal resistance of fluid, which is of great significance for the operation, material selection and leakage control of oil plugging. Although high viscosity materials have advantages in oil plugging, they also have disadvantages. They are difficult to operate, have poor fluidity, and are difficult to uniformly coat and fill complex leakage points, resulting in long construction time and high requirements for equipment. In low temperature environment, high viscosity materials are more difficult to operate, and may also affect the operation of equipment. Low viscosity materials have insufficient sealing, are easily washed away by external force, have too strong permeability, which may lead to material waste and environmental pollution, have long curing time and are sensitive to environment, which affects the plugging effect.
[0095] The amount of well wall reinforcing agent and the content of siloxane polymer and hydrophilic group will affect the viscosity of the drilling fluid. As can be seen from Table 1, the amount of well wall reinforcing agent is positively correlated with the viscosity of the drilling fluid. In the water-based slurry of Examples 4, 5, 6 and Comparative Example 1, although the amount of well wall reinforcing agent is different, the viscosity of the drilling fluid changes relatively little. This is because through careful optimization of the combination of siloxane polymer, quaternary ammonium salt group and hydrophilic group, good fluidity of the drilling fluid can be maintained at different amounts. This good fluidity is crucial for the performance of the drilling fluid, because it can ensure that the drilling fluid is effectively adsorbed on the surface of the rock formation, forming a uniform protective film, enhancing the stability of the well wall, and at the same time facilitating the entry of the drilling fluid into and plugging of the layered micro-cracks, thereby effectively reducing the risk of leakage.
[0096] II. Medium pressure filtration loss
[0097] The medium pressure filtration loss test was carried out on the samples before and after aging. The sample aging was carried out by rolling the sample at 180°C for 10h, and then cooling to room temperature. The test was carried out according to the standard in the chapter of Filtration in API RP 13B-1 Recommended Practice for Field Testing Water-based Drilling Fluids. The test results of the medium pressure filtration loss performance evaluation of the block copolymer well wall reinforcing agent with positively charged anchor points of the present application are shown in Table 2:
[0098] Table 2
[0099] Loss on filtration (ml) at room temperature Loss on filtration (ml) at 180°C Comparative Example One 15.5 17.3 Example Four 9.2 10.9 Example Five 9.8 11.2 Example Six Example Seven 10.2 12.5
[0100] The medium pressure filtration loss is an important indicator of the performance of the drilling fluid, which reflects the volume of liquid passing through a specific filter paper under certain pressure and time conditions. It is usually used to evaluate the filtration characteristics and the quality of the filter cake formed by the drilling fluid. In general, the smaller the filtration loss of the drilling fluid, the easier it is to form a low permeability, flexible, thin and dense filter cake, which is beneficial to the stability of the well wall and the protection of the oil and gas layer.
[0101] From the data analysis of Table 2, it can be clearly seen that the addition amount of the well wall strengthening agent and the content of the siloxane polymer have a significant influence on the medium filtration loss of the drilling fluid. Specifically, in the water-based slurry experiments of Example Four, Example Five, Example Six and Comparative Example One, the addition amount of the well wall strengthening agent and the medium filtration loss show a clear positive correlation. This indicates that as the addition amount of the well wall strengthening agent increases, the medium filtration loss of the drilling fluid also increases accordingly. However, it is worth noting that in Example Four, Example Five and Example Six, the combination of the siloxane polymer with the quaternary ammonium salt group and the hydrophilic group is carefully optimized, so that the drilling fluid in these experimental groups shows an ideal value in terms of medium filtration loss. This optimized formulation combination not only effectively controls the medium filtration loss, but also provides strong support for oil plugging operations, helps to improve the plugging effect and reduce the risk of leakage, thereby showing significant advantages in actual application.
[0102] III. Plugging performance test
[0103] By measuring the invasion depth of the drilling fluid in the sand bed, the effectiveness of the plugging agent in plugging the cracks and pores of the formation can be evaluated. The non-permeability tester (visual sand bed filtration instrument) is used to determine the plugging property of the base slurry and each drilling fluid according to the API specification. The test method is as follows: add sand with a particle size of 10-50 mesh in the cylinder of the visual sand bed filtration instrument, compact and flatten to form a sand bed, then slowly add 500 mL of base slurry or drilling fluid into the cylinder, stand for 10 min, measure the depth of the base slurry or drilling fluid immersed in the sand bed, then gradually pressurize to 0.69 MPa, measure the depth of the drilling fluid immersed in the sand bed after 10 min. The test results of the block copolymer well wall strengthening agent with positive charge anchor points of the present application for the plugging performance evaluation of water-based drilling fluid are shown in Table 3.
[0104] Table 3
[0105]
[0106] Plugging performance is a key indicator for measuring whether the drilling fluid can effectively prevent fluid leakage in actual application. It mainly evaluates the sealing ability of the drilling fluid when facing well wall cracks, small gaps and formation pores. Good plugging performance means that the drilling fluid can quickly and effectively fill these spaces to form a reliable barrier to prevent further loss of drilling fluid and other fluids, which is crucial for maintaining wellbore pressure balance, ensuring drilling safety and protecting oil and gas reservoirs from damage.
[0107] The results of the plugging performance test and the medium pressure filtration performance test are consistent, further verifying the effectiveness of the examples. In the plugging performance test, examples four, five and six exhibit excellent plugging capacity, which can effectively plug the tiny gap and reduce the loss of drilling fluid. In the medium pressure filtration performance test, these formulations also show a lower filtration loss. This consistent trend in the results shows that by reasonably adjusting the content and collocation of the well wall strengthening agent, the silicon-oxygen polymer and the hydrophilic group, the comprehensive performance of the drilling fluid can be significantly improved, which can exhibit better plugging effect and filtration control capacity in actual application, thereby showing significant advantages in oil plugging operations.
[0108] The above only describes the preferred embodiments of the present application, shows and describes the basic principles, main features and advantages of the present application, and does not limit the patent protection scope of the present application. It should be understood by those skilled in the art that the present application is not limited by the above examples. In addition to the above examples, other embodiments of the present application can be implemented without departing from the spirit and scope of the present application. The present application can also have various changes and improvements. Any technical solution formed by equivalent replacement or equivalent transformation falls within the scope of protection required by the present application. The scope of protection required by the present application is defined by the appended claims and their equivalents. The technical features of the present application not described herein can be implemented by or using existing technology, which will not be described here.
Claims
1. A block copolymer well strengthening agent rich in positive charge anchors, characterized by: The well wall reinforcing agent is a block copolymer formed by generating a siloxane bond polymer through acid catalyzed hydrolysis polymerization, and grafting a hydrophilic group and introducing a quaternary ammonium salt group in sequence.
2. The block co-polymer well strengthening agent of claim 1, wherein: The siloxane bond polymer is prepared by hydrolysis condensation reaction of silane monomers including dimethyldichlorosilane, dimethyldimethoxysilane or dimethyldiethoxysilane.
3. The block co-polymer well strengthening agent of claim 1, wherein: The molecular formula of dimethyldichlorosilane, dimethyldimethoxysilane and dimethyldiethoxysilane is respectively: The molecular formula of the siloxane bond polymer is:
4. The block co-polymer well strengthening agent of positive charge rich anchor points according to claim 1, characterized in that: The hydrophilic group is polyethylene glycol or polypropylene glycol, and the molecular formula is respectively:
5. The block co-polymer well strengthening agent of claim 1, wherein: The quaternary ammonium salt group is dimethyldiallylammonium chloride, hydroxyethyltrimethylammonium chloride or hydroxyethyltriethylammonium chloride, and the molecular formula is respectively:
6. A method of preparing a block copolymer well strengthening agent rich in positive charge anchor points, characterized in that, The steps in sequence include: S1, preparing a siloxane polymer; S2, preparing a quaternary ammonium siloxane polymer; S3, grafting a hydrophilic group; S4, further introducing a quaternary ammonium salt group to synthesize the block copolymer with rich positive charge anchor points.
7. The method of claim 6, wherein the method is characterized by, The specific preparation process of the siloxane polymer in step S1 is as follows: dimethyldichlorosilane or dimethyldimethoxysilane or dimethyldiethoxysilane is subjected to acid catalyzed reaction with dimethylhydrochlorosilane or dimethylhydroxymethoxysilane or dimethylhydroxyethoxysilane in a solvent, the solvent is dichloromethane or toluene, after acid catalyzed reaction, the acid water layer is separated by standing and removing; then the oil layer is repeatedly washed with distilled water until the pH value of the washing water is 7; finally, the oil layer is dried under vacuum to remove the contained water, and the siloxane polymer is obtained.
8. The method of claim 7, wherein the method is characterized by, In step S1, the molar ratio of silane monomer to hydrogen-containing silane is (5-20):2; the acid catalyst is hydrochloric acid or sulfuric acid, and the amount is 10%-20% of the mass of the reaction system, and the reaction time is 5-8 hours.
9. The method of claim 7, wherein the method is characterized by, The reaction process of generating the siloxane polymer is respectively as follows:
10. The method of claim 6, wherein the method is characterized by: In step S2: dichloromethane or toluene is used as the solvent, the siloxane polymer obtained in step S1 is subjected to double bond addition reaction of silane hydrogen bond under the catalysis of chloroplatinic acid with dimethyldiallylammonium chloride, and a quaternary ammonium siloxane polymer is obtained.
11. The method of claim 10, wherein the method is characterized by, In step S2: the molar ratio of the siloxane polymer to the quaternary ammonium salt group is (2-6):1, the amount of the chloroplatinic acid catalyst is 3ppm-6ppm, and the reaction time is 4-6 hours.
12. The method of claim 10, wherein the method is characterized by, The reaction process of generating the quaternary ammonium siloxane polymer is as follows:
13. The method of claim 6, wherein the method is characterized by, In step S3: dichloromethane or toluene is used as the solvent, the quaternary ammonium siloxane polymer obtained in step S2 is subjected to reaction under the catalysis of sodium ethoxide or sodium methoxide with the hydrophilic group polyethylene glycol or polypropylene glycol, and a quaternary ammonium siloxane polymer grafted with the hydrophilic group is obtained.
14. The method of claim 13, wherein the method is characterized by, In step S3: the molar ratio of the quaternary ammonium siloxane polymer to the hydrophilic group is 1:2, the catalytic reaction is carried out under the action of sodium methoxide or sodium ethoxide at 80-100℃ for 5-8 hours, and the amount of the catalyst is 5%-15% of the mass of the reaction system.
15. The method of claim 13, wherein the method is characterized by: The reaction process of grafting the hydrophilic group is as follows:
16. The method of claim 6, wherein the method is characterized by, In step S4: dichloromethane or toluene is used as the solvent, the quaternary ammonium siloxane polymer grafted with the hydrophilic group is subjected to reaction under the catalysis of sodium hydroxide with the quaternary ammonium salt group hydroxyethyltrimethylammonium chloride or hydroxyethyltriethylammonium chloride, and the block copolymer with rich positive charge anchor points is obtained.
17. The method of claim 16, wherein the method is characterized by, In step S4, the molecular formula of hydroxyethyl trimethyl ammonium chloride and hydroxyethyl triethyl ammonium chloride are respectively: The molar ratio of the grafted hydrophilic group quaternary ammonium siloxane polymer and quaternary ammonium salt group is 1:2, the catalyst used is 5-10% sodium hydroxide and the reaction is carried out at 80-100°C, 5MPa for 5-8 hours.
18. The method of claim 16, wherein the method is characterized by, In step S4, the further introduction of quaternary ammonium salt group synthesis process is as follows:
19. Use of the block co-polymer well strengthening agent of rich positive charge anchor point as claimed in any one of claims 1-4 in the preparation of water-based drilling fluid, characterized in that, The well wall reinforcing agent is added into the water-based drilling fluid, and the well wall reinforcing agent is added in an amount of 3-6% of the total mass of the water-based drilling fluid, which is used for well wall reinforcement and plugging in shale formation.
Citation Information
Patent Citations
Well wall strengthening agent composition and water-based drilling fluid and preparation method thereof
CN118652671B
Film-forming enhancer for water-based drilling fluid, preparation method of film-forming enhancer and slim-hole reservoir protection drilling fluid
CN120647863A